Single droplet separations and surface partition coefficient measurements using laser ablation mass spectrometry - Jorabchi, Kaveh (2009)
Surface activity of analytes plays a significant role in many chemical and physical phenomena. We present here a mass spectrometric method to characterize surface activity and solute partitioning between bulk liquid and the gas-liquid interface in droplets. The approach employs ablation by an IR laser from the surface of a microliter droplet deposited on a stainless steel post. The ablated material is ionized for mass spectrometric analysis by either droplet charging or by post-ionization in an electrospray plume. Three areas of application have been explored using this method; 1) separations in a single droplet: continuous ablation by a series of many successive laser pulses results in faster depletion of more surface active analytes, effectively comprising a surface activity-based separation. 2) Partition coefficient measurements: droplet volume is held constant during ablation by continually replenishing lost solvent. This leads to analyte-specific ion signal decay curves that may be fitted to a model based on Langmuir adsorption isotherms and simple analytical expressions, yielding quantitative values for the analyte surface partition coefficients. 3) Studies of the relationship between surface partitioning and HPLC phase partitioning: comparisons of surface activities measured by laser desorption with retention times in reversed phase HPLC reveal that the relationship between the two partitioning processes is very sensitive to chemical structure. Poor correlation between the retention time and surface activity is also observed within a subcategory of analytes (peptides). This effect is attributed to multi-modal solute-stationary phase interactions. The laser desorption approach presented here provides direct information on analyte surface activities free from the complications encountered in chromatographic methods due to chemical structure variations.